Comment, Rating, Opinion, Review – the Preliminary Research - Jaworska, Monika (Respectus Philologicus, 2021)
The article focuses on functional speech genres used on the Internet to assess the level of customer satisfaction after purchasing goods and services on portals with various offers. It attempts to define what genre is used in the texts called commentaries, evaluations, opinions and consumer reviews. Both Internet users and providers of goods and services use these terms interchangeably. The situation may result from the fact that in the ordinary mind, they constitute one genre. The text introduces the research on the statements of internet users expressing their opinion on the transaction, the purchased products, and the service provided. Nowadays, the Internet has such a large social impact that it is important to examine the changes in speech genres existing in the Internet space in relation to their prototypes derived from the literary tradition.
Keywords: speech genre; comment; rating; opinion; consumer review